2022
DOI: 10.1155/2022/5358546
|View full text |Cite|
|
Sign up to set email alerts
|

Research on English Hybrid Assisted Teaching System Using Contextual Support of R-CNN

Abstract: The developing countries and developed countries are depending on major as well as single language, i.e., English. The software tool level English teaching assistance models are available but those are not that user-friendly and also unable to support current technology. The earlier English teaching assistance techniques like RFO (Random Forest Optimization) machine learning, Xboosting machine learning, and SVM (Support Vector Machine) cannot support background provision. English teachers must find a way to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
(20 reference statements)
0
7
1
Order By: Relevance
“…When applying scaffolding to the field of education, instructional scaffolding must ensure the following characteristics [3; 13]: learning support activities must have continuity [15]. When teachers apply learning support activities, it is necessary to set up a timetable as well as clearly explain the sequence of activities, and various factors in blending learning environments for learners to get used to and must maintain this activity regularly throughout the teaching process, like incorporating dialogue and digital tools in educational settings [13; 24]; learning support activities must be done in the context, the situation (contextual support like blending learning environments) [32], in accordance with Vygotsky's principle (Zone of Proximal Development [14; 39]. According to Vygotsky, Actual Developmental Level is an individual's current level of development, as measured by an individual's ability to solve problems alone or with support from others.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…When applying scaffolding to the field of education, instructional scaffolding must ensure the following characteristics [3; 13]: learning support activities must have continuity [15]. When teachers apply learning support activities, it is necessary to set up a timetable as well as clearly explain the sequence of activities, and various factors in blending learning environments for learners to get used to and must maintain this activity regularly throughout the teaching process, like incorporating dialogue and digital tools in educational settings [13; 24]; learning support activities must be done in the context, the situation (contextual support like blending learning environments) [32], in accordance with Vygotsky's principle (Zone of Proximal Development [14; 39]. According to Vygotsky, Actual Developmental Level is an individual's current level of development, as measured by an individual's ability to solve problems alone or with support from others.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Hybrid learning (HL) was practiced long before the Coronavirus Disease 2019 (COVID-19) pandemic spread in many departments and courses. Recent studies of HL have reported variant evidence, variables of HL, and subjects (Anabel & Simanjuntak, 2022;Criollo-C et al, 2022;Dodiya, 2021;Doghonadze et al, 2021;Sunardi & Lutfi, 2022;Utami et al, 2020;Xiaodong, 2022;Yuan, 2022). However, the studies left limitations and gaps.…”
Section: Introductionmentioning
confidence: 99%
“…Xiaodong (2022) reported an experimental study that focused on a "hybrid online and offline English-speaking teaching method based on modern educational technology" in China (p. 1). Yuan (2022) reported an experiment study of a Region-based convolutional neural network (R-CNN)-based artificial neural network (ANN) that focuses on improving the performance of English hybrid-assisted teaching and comparing the performance of the proposed system with known nearest neighbor (KNN), random forest optimization (RFO), and Xboosting in China. Sunardi and Lutfi (2022) also reported their survey study that focuses on 203 students' experience in learning English with HL and their perception of how HL influences their learning of English in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%